Increasing Brand Loyalty Through Cultivating Brand Love (International Journal of Scientific Research and Management (IJSRM), 2024)
The purpose of this study is to ascertain how customer value, customer satisfaction, and customer experience relate to brand love and brand loyalty. The research population comprises Starbucks customers as of December 2023. Purposive sampling, which involved selecting customers who had made purchases more than twice, was the sample strategy employed. A total of 250 people’s data were gathered. SEM is the data analysis technique employed in this study with Smart PLS assistance. The study’s findings indicate that brand love is influenced by customer value, customer satisfaction, and customer experience. Brand loyalty affects the brand. Brand loyalty is unaffected by customer value, customer satisfaction, or customer experience. According to these findings, a brand that is well-regarded by consumers would offer positive value on the presumption that the product or service fulfills their needs and gives them a satisfying experience. This will lead to customer love for the brand but not brand loyalty.